Análise da formação continuada de professores de geografia no PDE: um estudo dos orientandos da UNIOESTE - Francisco Beltrão - Farias, Sérgio André (2013)
The study initiates with an analysis of the role of the State in the logic of Capitalism and its contributions to other educational policies of continued formation of teaching class. Regarding the State, one can understand that, even though it s an institution who serves the dominant class, it s an monolithic institution with sort of relative autonomy. Depending of the strength correlation between social classes, it is possible that educational policy can be established in the State by the working class. It is inside of this context that we sought to study the Educational Policy of PDE/PR. The research aimed to analyze the Educational Development Program PDE/PR as a Continued Formation of teachers in Geography discipline with a guidance of UNIOESTE Francisco Beltrão from 2007 to 2010. This Public Policy represents an important accomplishment to the teaching class of the state of Paraná, result of the struggle and participation, specifically the APP Syndicate along with the SEED, having as the result the regularization of the PDE/PR Program as public policy. Significant conquests can be noticed in teaching formation, specially in theory/practice articulation and material conditions for this study, however the fact that the State is the manager of the program presents certain contradictions. The PDE/PR Program is presented as an innovative Continued Formation, considering the approximation of teachers to the scientific theories of initial graduation, even though the emphasis in teaching methodology prevails. The analysis of Continued Formation of Geography Teachers mentored by UNIOESTE-FB, sought to evaluate both value and improvement of basic education PDE teachers, concerning the access to knowledge and its reflections through the IES; the thoughts about school practicing; the exchange of experiences; the sharing of knowledge; the professional development and the continuity in daily school. The qualitative interviews of the study proved that the Program has contributed to increase the intellectual level of Geography PDE s teachers, although, in a general context, some contradictions can be found in teachers formation policy.